An RNA tertiary structure in the 3' untranslated region of enteroviruses is necessary for efficient replication. - Mirmomeni, M H (1997)
RNA tertiary structures, such as pseudoknots, are known to be biologically significant in a number of virus systems. The 3' untranslated regions of the RNA genomes of all members of the Enterovirus genus of Picornaviridae exhibit a potential, pseudoknot-like, tertiary structure interaction of an unusual type. This is formed by base pairing between loop regions of two secondary structure domains. It is distinct from a potential, conventional pseudoknot, studied previously in poliovirus, which is less conserved phylogenetically. We have analyzed the tertiary structure feature in one enterovirus, coxsackievirus A9, using specific mutagenesis. A double mutant in which the potential interaction was destroyed was nonviable, and viability was restored by introducing compensating mutations, predicted to allow the interaction to reform. Phenotypic pseudorevertants of virus mutants, having mutations designed to disrupt the interaction, were all found to have acquired nucleotide changes which restored the potential interaction. Analysis of one mutant containing a single-base mutation indicated a greatly increased temperature sensitivity due to a step early in replication. The results show that, in addition to secondary structures, tertiary RNA structural interactions can play an important role in the biology of picornaviruses.